Blockade of adipocyte differentiation by cordycepin - Takahashi, Shuhei (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: Cordyceps militaris has the potential to suppress differentiation of pre-adipocytes. However, the active entities in the extract and the underlying mechanisms of its action are not known. Hence, we investigated whether and how cordycepin (3′-deoxyadenosine), a constituent of C. militaris, inhibits adipogenesis. EXPERIMENTAL APPROACH: Differentiation of 3T3-L1 pre-adipocytes and pre-adipocytes in primary cultures was induced by Insulin, dexamethasone and IBMX, and these were used as in vitro models of adipogenesis. The effects of cordycepin on adipogenesis were examined with particular focus on the regulation of CCAAT/enhancer-binding protein β (C/EBPβ) and PPARγ. KEY RESULTS: Cordycepin suppressed the lipid accumulation and induction of adipogenic markers that occurred on differentiation of pre-adipocytes and also blocked the down-regulation of a pre-adipocyte marker. This anti-adipogenic effect was reversible and mediated by an adenosine transporter, but not A(1), A(2) or A(3) adenosine receptors. This effect of cordycepin was not reproduced by other adenosine-related substances, including ATP, ADP and adenosine. Early induction of the adipogenic C/EBPβ–PPARγ pathway was suppressed by cordycepin. Blockade of mTORC1 via inhibition of PKB (Akt) and activation of AMP kinase was identified as the crucial upstream event targeted by cordycepin. In addition to its negative effect on adipogenesis, cordycepin suppressed lipid accumulation in mature adipocytes. CONCLUSIONS AND IMPLICATIONS: These results suggest that the anti-adipogenic effects of cordycepin occur through its intervention in the mTORC1-C/EBPβ–PPARγ pathway. Cordycepin, by blocking both adipogenesis and lipid accumulation, may have potential as a therapeutic agent for effective treatment of obesity and obesity-related disorders.